Transport development in Asian megacities a new perspective - Morichi,Shigeru; Acharya,Surya Raj; SpringerLINK eBooks - English/International Collection (London Springer, 2013)
Annotation This title explores the challenges of rapid urban population growth in Asia to transport planners, including management of infrastructure and services in megacities and shrinking urban mobility due to sharply rising vehicle numbers and inadequate, poorly managed roads.
Scholarly & Professional